Biodegradable Electrohydraulic Soft Actuators - Ryo Kanno; Fabio Caruso; Kazuma Takai; Yegor Piskarev; Vito Cacucciolo; Jun Shintake (Advanced Intelligent Systems, 2023)
Biodegradable materials decompose and return to nature. This functionality can be applied to derive robotic systems that are environmentally friendly. This study presents a fully biodegradable soft actuator, which is one of the key elements in “green” soft robotics. The working of the actuator is based on an electrohydraulic principle, which is similar to that of hydraulically amplified self‐healing electrostatic actuators. The actuator developed in this study consists of a dielectric film made of polylactic acid (PLA) and polybutylene adipate‐co‐terephthalate (PBAT), with soybean oil as the dielectric liquid and electrodes made from a mixture of gelatin, glycerol, and sodium chloride (NaCl). The synthesized biodegradable electrode material exhibits a Young's modulus of 0.06 MPa and resistivity of 258 Ω·m when the mass fraction of NaCl relative to the amount of gelatin and glycerol is 10 wt%. The softness and resistivity of the electrode material results in actuation strain values of 3.2% (at 1 kV, corresponding to 1.2 kV mm−1) and 18.6% (at 10 kV, corresponding to 9.6 kV mm−1) for the linear‐type and circular‐type actuators, respectively. These values obtained for the biodegradable electrohydraulic soft actuators are comparable to those of nonbiodegradable actuators of the same type, representing the successful implementation of the concept.